Balancing Tradition and Science in Preventing Snakebite Envenoming among Beekeepers in Baringo County, Kenya: A Systematic Review through a Risk Compensation Lens - Caroline M. Lisanza; Wilson A.P. Otengah (African Journal of Education,Science and Technology (AJEST), 2025)
Snakebite envenoming (SBE) is a significant yet often overlooked occupational hazard among beekeepers, particularly in regions with high snake prevalence. Despite the known risks, preventive measures and response strategies vary widely due to differences in knowledge, cultural beliefs, and access to healthcare. This paper examines SBE prevention and response as they pertain to beekeepers in Baringo County, Kenya, drawing on a systematic review of global, regional, and national literature through the lens of risk compensation theory (RCT), which explores how perceived risk and protective measures influence behavior. The systematic review was conducted to synthesize existing knowledge, prevention, and intervention strategies for SBE among beekeepers, given the limited literature focused specifically on Baringo County. Findings were categorized into three key themes: (1) knowledge and awareness, (2) preventive strategies, and (3) intervention and response mechanisms. The review revealed that while beekeepers recognize the threat of snakebites, their knowledge is often shaped by traditional practices rather than biomedical guidelines. Preventive strategies varied, with many relying on traditional deterrents and others adopting modern safety measures such as hive placement and protective clothing. However, cost and accessibility remained barriers to widespread adoption. In response to envenomation, many beekeepers initially seek treatment from traditional healers, delaying access to life-saving anti-venom. This behavioral pattern aligns with RCT, where reliance on perceived protective measures, whether traditional or biomedical, influences risk-taking and response behaviors. These findings underscore the need for culturally sensitive interventions that integrate traditional knowledge with evidence-based strategies to enhance SBE prevention and response. Increasing access to protective equipment, improving healthcare infrastructure, and implementing community-based training can bridge the gap between awareness and effective risk mitigation. By addressing economic and logistical barriers, a more comprehensive approach to SBE prevention can be achieved, ultimately reducing morbidity and mortality among beekeepers in Baringo County and other snake-endemic regions.